Birth order and pediatric traumatic brain injury - Omer, Mazin; Posti, Jussi P.; Gissler, Mika; Merikukka, Marko; Bärnighausen, Till; Wilson, Michael (Scientific reports, 2022)
Pediatric traumatic brain injury (TBI) is a significant problem of public health importance worldwide. Large population-based studies on the effect of birth order on health phenomena are exceedingly rare. This study examines the relationship between birth order and risk for pediatric TBI among sibling groups. We performed a retrospective cohort study following 59,469 Finnish newborns from 1987 until age 18 years. Data on first diagnosis of TBI was recorded within the 1987 Finnish Birth Cohort (FBC). Compared with first born siblings, later born siblings had an increased risk of TBI during the follow-up period (hazard ratio [HR] 1.02; 95% confidence interval [CI] 0.91-1.14 for second born, HR 1.09; 95% CI 0.95 1.26 for third born, HR 1.28; 95% CI 1.08-1.53 for fourth or higher). When adjusted for sex and maternal age at child’s birth, HRs (95% CIs) for TBI during the follow-up period were 1.12 (0.99-1.26) for second born, 1.31 (1.12-1.53) for third born and 1.61 (1.33-1.95) for fourth born or higher children, respectively. Within this large register-based population-wide study, order of birth modified risk for pediatric TBI among sibling groups. Taken together, these study findings may serve to stimulate further inquiry into genetic, psychological, or psychosocial factors which underlie differences in risk and depth of effect within and between sibling groups.
Gesehen am 27.10.2022